NATURE IN "A SINGLE ROSE" BY MURIEL BARBERY - Yurechko, Daryna (SWorld-Ger Conference proceedings, 2023)
The article is devoted to the study of the artistic features of the images of nature in M. Barberi’s novel "The Lonely Rose". It was found that various images of nature are an important segment of the urban space of Kyoto. It is shown that the process of